Short term outcomes of combined pars plana vitrectomy for epiretinal membrane and phacoemulsification surgery with multifocal intraocular lens implantation - Patel SB (Dove Medical Press, 2019)
Sunny B Patel,1 Michael E Snyder,1,2 Christopher D Riemann,1,2 Robert E Foster,1,2 Robert A Sisk1,2 1Department of Ophthalmology, University of Cincinnati, Cincinnati, OH, USA; 2Cincinnati Eye Institute, Cincinnati, OH, USA Purpose: The purpose of this study was to evaluate the functional and anatomical outcomes of combined phacovitrectomy with multifocal intraocular lens (mfIOL) implantation.Methods: Retrospective, interventional, non-comparative case series of six eyes that received a combined phacoemulsification surgery with apodized, diffractive mfIOL implantation for cataract and pars plana vitrectomy (PPV) with membrane peeling for epiretinal membrane (ERM). Outcome measures included distance and near visual acuities (DVA and NVA), central macular thickness (CMT), intraocular pressure (IOP), and disruption of external limiting membrane (ELM) or inner-segment outer-segment (IS/OS) junction.Results: Mean logMAR glare DVA improved from 0.40 (Snellen 20/50) preoperatively to a mean uncorrected DVA of 0.038 (Snellen 20/22) (P=0.004) at 6 months after surgery. All eyes achieved NVA of J2 or better by 12 months postoperatively. Median CMT improved by 10 µm and mean IOP increased by 1 mmHg at 12 months postoperatively. Percentage of patients with ELM or IS/OS disruptions decreased from 66.7% to 33.3%. Two eyes demonstrated residual metamorphopsia on Amsler grid testing postoperatively. Postoperatively, four eyes required laser capsulotomy and one required LASEK for refractive correction.Conclusion: Combined phacovitrectomy, membrane peeling, and mfIOL implantation improved VA in patients with idiopathic ERM. Multifocality was achieved, but final visual outcome was delayed due to posterior capsular opacification and macular healing. Keywords: cataract, combined, epiretinal membrane, multifocal intraocular lens, phacoemulsification, phacovitrectomy